Mitigasi Risiko Rantai Pasok Sayur Organik di CV. XY dengan Metode HOR (House of Risk) - Muzdalifa Tiin Maezura; Vamya Zolafa Yesfy; Muhammad Rifqi Alauddin; Dwi Laila Maulida MAULIDA (Politeknik Pembangunan Pertanian Malang, 2025)
This study aims to analyze and identify risks in the organic vegetable supply chain distribution at CV. XY Surabaya using the House Of Risk (HOR) method. The main prblems faced by the company include fluctuating demand, delivery delays, product demage, and order mismatches. The HOR method is employed to identify risk agents and prioritize mitigation strategies. The results show that the highest ARP values are found in crop failure, careless human resources, and mismatched producs. The recommended priority mitigation strategies include employee training, competent staff selection, and strict sorting and grading SOPs before delivery. The application of the HOR method has proven effective in formulating afficient and preventive actions to minimize potential losses caused by supply chain risk